Radical Orthodoxy: An Appreciation - Burrell, David B. (Philosophy & theology, 2004)
The author presents a brief appreciation of the merits of the Radical Orthodoxy movement. That appreciation centers on four themes: (1) theology as sacra doctrina, (2) countering secular reason in its latest avatar of “post-modernism,” (3) Radical Orthodoxy’s offering a theology of culture, and (4) the Thomism of Radical Orthodoxy. The author concludes with some remarks concerning the reception of Radical Orthodoxy in the United States.